Sunnah Dan Peranannya Dalam Penetapan Hukum Islam : Sebuah Pembelaan Kaum Sunni - SIBA'I, Musthafa Al (Pustaka Firdaus, 1991)
Sunnah Dan Peranannya Dalam Penetapan Hukum Islam : Sebuah Pembelaan Kaum Suni